Development of a Resonant High Power Charging Station for Fleet Vehicles - (:unkn) unknown (My University, 2019)
C onventional vehicles chargers are based on plugging the car battery using wire to the electricity grid through some conversion levels. In general, this system is an interface between the AC grid and the battery which requires DC voltages. The focus of this research is on wireless power charging technology. The wireless configuration benefits the system by providing electric isolation between transmitter and receiver side, and by making the charging process more convenient for the users. One major drawback of the wireless charging systems in compare to the conventional system is the lower efficiency of these systems. The resonant high power charging configuration of this study is designed to tackle this problem by enabling soft switching to minimize the switching loss. In this research a resonant LLC configuration is used for the EV charging application. The configuration and the step by step design of the resonant circuit is illustrated and analyzed. Also, other different topologies of the wireless charging systems have been introduced and compared with the proposed topology. The converter is modeled and simulated for different modes of operation. The optimal frequency selection which is dictated by the resonant circuit and magnetic design is obtained based on the mathematical model of the circuitry. The simulation results show that the designed converter improves the efficiency significantly using the resonant wireless charging configuration.